2018
DOI: 10.1007/s40751-018-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Inspectable Student Models and Didactics of Statistics

Abstract: Statistics is a challenging subject for many university students. In addition to dedicated methods of didactics of statistics, adaptive educational technologies can also offer a promising approach to target this challenge. Inspectable student models provide students with information about their mastery of the domain, thus triggering reflection and supporting the planning of subsequent study steps. In this article, we investigate the question of whether insights from didactics of statistics can be combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The student model design was evaluated in two earlier courses (Tacoma, Sosnovsky, Boon, Jeuring, & Drijvers, 2018). Participants in the current study had been enrolled in one of these earlier courses and, consequently, were already familiar with inspectable student models.…”
Section: Methodsmentioning
confidence: 99%
“…The student model design was evaluated in two earlier courses (Tacoma, Sosnovsky, Boon, Jeuring, & Drijvers, 2018). Participants in the current study had been enrolled in one of these earlier courses and, consequently, were already familiar with inspectable student models.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies revealed that students value the presence of inspectable student models in weekly homework sets (Mitrovic & Martin, 2007;Tacoma, Sosnovsky, Boon, Jeuring, & Drijvers, 2018). To our knowledge, previous research focused on the effects of inspectable student models combined with either (1) task selection adapted by the electronic learning environment based on the content of the student model (e.g., Brusilovsky, Sosnovsky, & Yudelson, 2009), or (2) monitoring of and feedback on task selection by the student (Mitrovic & Martin, 2007).…”
Section: Inspectable Student Models In Electronic Learning Environmentsmentioning
confidence: 99%
“…Most tasks in the homework sets were connected to the topic(s) they were related to. Lists of topics, connections between tasks and topics and the tasks themselves were optimized informed by findings by Tacoma et al (2018), based on the same course in the previous academic year. In particular, this previous study showed that some tasks served a useful function in the homework set (such as introducing a new topic), but were not appropriate for informing student models, and hence should Fig.…”
Section: Design and Implementation Of The Inspectable Student Modelsmentioning
confidence: 99%
“…Al respecto, Cobb (2007) sugiere que la modelación debería desempeñar un papel importante en la enseñanza de la estadística, afirmando que todos los métodos estadísticos se derivan de un modelo y que uno de los propósitos de la educación matemática es fomentar el pensamiento estadístico en los estudiantes a través de un razonamiento explícito entre el modelo y la realidad. El desarrollo de la modelación estadística ayuda a enfrentar las dificultades de aprendizaje de la estadística, permitiendo al estudiante desarrollar la capacidad de resolución de problemas (Tacoma et al, 2018).…”
Section: Introductionunclassified